PENGARUH BUDAYA KERJA TERHADAP KINERJA PEGAWAI DINAS PETERNAKAN DAN PERKEBUNAN KABUPATEN LAMPUNG TENGAH - Fani Handayani; M. Yusuf Sulfarano Barusman; M Oktaviannur (Universitas Bandar Lampung (UBL), 2021)
The purpose of this study was to determine the effect of work culture on employee performance at the Livestock and Plantation Service Office of Central Lampung Regency. This type of research is a descriptive research type, with a survey method approach, with a population of all 80 employees of the Livestock and Plantation Service Office of Central Lampung Regency, as well as the research sample. The data analysis technique used the data instrument test analysis, simple linear regression. Based on the results of the calculation, work culture has a positive and significant effect on the performance of employees at the Livestock and Plantation Service Office of Central Lampung Regency, it is that if the work culture is improved, the employee's performance will increase better. The ability of the independent variables, namely work culture (X), is able to explain the variation in employee performance values by 53.8%. Meanwhile, the remaining 46.2% is not influenced by work culture, but can be influenced by various other variables not discussed in the study